Inovasi Produk Metode Manual Brew Aero Press Di Re.Kreasi Coffee - Sahrul Fat K. Pandjo; Juliana Kadang; Erwan Sastrawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The rise of the culinary business in the coffee shop sector in Palu City has increased business competition rapidly, requiring business actors to be competitive. Therefore Re.kreasi coffee needs to formulate the right business model and requires a new strategy in order to achieve competitive advantage. The purpose of this activity is to find out the product innovation of the manual brew aero press method on Re.kreasi coffee. The analytical tool used to solve the problem is a business SWOT analysis. The result of this study is that the results of the SWOT analysis test show that the right strategy for the market phenomenon faced by Re.kreasi coffee is product innovation. The selected product is Aero Press using the manual brew processing method. During the four months it was implemented, it had a positive impact on Re.kreasi coffee, both operational performance, competitive advantage and revenue from sales of Aero Press products.